2006
DOI: 10.1002/chem.200600001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure and Magnetic properties of Chiral and Nonchiral Transition‐Metal Malates

Abstract: Carboxylate-bridged complexes of transition metals, M(II)=Mn(II), Fe(II), Co(II), Ni(II), Zn(II), were synthesised by reaction of M(II) salts with dl-malate and L-malate under hydrothermal conditions. These complexes form four series of compounds, which have been fully characterised structurally, thermally and magnetically. The crystal structures of the new chiral compounds, [Mn(L-mal)(H(2)O)] (1), [Fe(L-mal)(H(2)O)] (2), [Co(L-mal)(H(2)O)] (3) and [Zn(L-mal)(H(2)O)] (4) as well as those of the bimetallic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 74 publications
3
41
0
Order By: Relevance
“…In the case of cobalt-based chiral polymers, a significant dichroism signature is observed in the 450-629 nm region, which corresponds to the 4 T 1g (F) Ǟ 4 T 1g (P) (ν 3 ) transition of Co 2+ ions located in an octahedral environment. [31,[41][42][43] The deviation from a symmetric shape of opposite signals in CD spectra between I L (Co) and I D (Co) is likely to be related to uncertainties in the background correction because the latter is very sensitive to small differences in the thickness and transparency of KBr pellets. Unfortunately, the presence of perchlorate ions in these compounds does not allow one to apply the strong pressure that is indispensable to fabricating KBr pellets of good quality.…”
Section: Complexes Based On Manganese(ii) Ionmentioning
confidence: 98%
See 3 more Smart Citations
“…In the case of cobalt-based chiral polymers, a significant dichroism signature is observed in the 450-629 nm region, which corresponds to the 4 T 1g (F) Ǟ 4 T 1g (P) (ν 3 ) transition of Co 2+ ions located in an octahedral environment. [31,[41][42][43] The deviation from a symmetric shape of opposite signals in CD spectra between I L (Co) and I D (Co) is likely to be related to uncertainties in the background correction because the latter is very sensitive to small differences in the thickness and transparency of KBr pellets. Unfortunately, the presence of perchlorate ions in these compounds does not allow one to apply the strong pressure that is indispensable to fabricating KBr pellets of good quality.…”
Section: Complexes Based On Manganese(ii) Ionmentioning
confidence: 98%
“…Model 1 [43] Model 2 [50] Model 3 [52] Model 4 [56] I L (Ni) Table 4. Single-crystal X-ray data collection details and refinement results.…”
Section: Complexes Based On Manganese(ii) Ionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17,18] In the case of cobalt, we demonstrated that condensation of the inorganic species increased with increasing temperature and pH, and this led to seven cobalt succinate topologies. [18] Comparison of these compounds to known nickel succinates indicates that the phases that occur at lower temperatures tend to be isostructural (consistent with other Co II and Ni II coordination polymers) [19,20] while the hydrothermal phases differ significantly. In particular conditions used for synthesizing the cobalt structure MIL-9, [21][22][23] which exhibits a 2D array of metal octahedra, gave a remarkable 3D inorganic framework when applied to nickel.…”
mentioning
confidence: 80%